The Situation Specific Arousal Analyzer: Innovation in the Physiological Assessment of Foreign Language Education Anxiety - Rivers, Damian J. (Frontiers in Education, 2022)
As the most studied affective variable within foreign language education, the emotion of anxiety continues to generate significant research interest. Owing to technological developments in wearable research devices, new opportunities have arisen to expand the research methodologies used in the recording and assessment of foreign language education anxiety. This article contends that foreign language education research has over-emphasized the experiential component of emotion while neglecting the behavioural and physiological components. Attention is first given to the emergence of emotion as a significant focal point in foreign language education. The position of anxiety as an affective variable in foreign language education is then documented along with the methodological limitations of experiential measures. The article then highlights technological innovations in physiological data measurement and analysis in the form of the Empatica E4 wristband and the recent development of the Situation Specific Arousal Analyzer (SSAA) application. The article demonstrates how foreign language education anxiety researchers can use the Empatica E4 and SSAA to document autonomic nervous system arousal in real-time communication situations using high-integrity metrics such as heart rate variability (HRV) and electrodermal activity (EDA) under a range of tailored conditions. The article ends with a call to foreign language education anxiety researchers to extend their methodological repertoire beyond experiential self-report measures and to consider the opportunities afforded by physiological data capture and analysis technologies.